2016
DOI: 10.1016/j.bandl.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Regularity and beyond: Impaired production and comprehension of inflectional morphology in semantic dementia

Abstract: Studies on inflectional morphology in semantic dementia (SD) have focused on the contrast between the regular and the irregular English past-tense. These studies aimed to contrast the claims of single- and dual-mechanism theories. However, both theories can account for impaired production of irregular verbs observed in SD. According to the dual-mechanism theory, this impairment is related to word-retrieval difficulties, while according to single-mechanism theory it is the consequence of semantic impairment. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Thus, although regular words with complex OPM can be correctly read through sublexical processes, their reading might be facilitated by the use of the whole-word reading network. Interestingly, Auclair-Ouellet et al (2016) found that the semantic impairment in svPPA patients affected morphological processes for both exception and regular verbs. Thus, the degradation of semantic knowledge conveyed by units such as morphemes or graphemes would not solely impact exception word processing but also regular words with complex OPM.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although regular words with complex OPM can be correctly read through sublexical processes, their reading might be facilitated by the use of the whole-word reading network. Interestingly, Auclair-Ouellet et al (2016) found that the semantic impairment in svPPA patients affected morphological processes for both exception and regular verbs. Thus, the degradation of semantic knowledge conveyed by units such as morphemes or graphemes would not solely impact exception word processing but also regular words with complex OPM.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons put forward to explain those difficulties included impairments of rule processing or lexical retrieval ( Pinker, 1998 ), which would be related to impairments of procedural and declarative memory, respectively ( Ullman et al, 1997 ). Because the double dissociations in regular and irregular verb impairment put forward by these models were not systematically observed (e.g., Faroqi-Shah and Thompson, 2004 , 2007 ; Faroqi-Shah, 2007 ; Macoir et al, 2013 ; Auclair-Ouellet et al, 2016 , 2018 ), other models suggested that the difficulties were related to phonological or semantic processing impairments (e.g., Joanisse and Seidenberg, 1999 ; McClelland and Patterson, 2002 ; Faroqi-Shah and Thompson, 2004 , 2007 ; Bastiaanse et al, 2011 ). Regarding the latter explanation, it was proposed to explain difficulties mostly when producing the past tense of irregular verbs in English, but a few studies considered a more conceptual contribution to morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Psycholinguistic models of inflectional morphology generally explain deficits in terms of rule-processing impairments, phonological-encoding impairments, lexical-retrieval impairments, or reductions in cognitive resources (e.g., Ullman et al, 1997 ; Pinker, 1998 ; Faroqi-Shah and Thompson, 2004 , 2007 ; Bastiaanse et al, 2011 ). However, studies of patients with post-stroke aphasia and primary progressive aphasia (PPA) suggest that those difficulties may be related to semantics, and more specifically to time conceptualization (e.g., Bates and Wulfeck, 1989 ; Auclair-Ouellet et al, 2016 ; Mack et al, 2021 ). Because it is known that semantic difficulties in AD become more severe with the progression of the disease, the question of whether time reference impairments may emerge as a result of time conceptualization impairments can be asked.…”
Section: Introductionmentioning
confidence: 99%
“…AD patients were recruited in Quebec City (Quebec, Canada) in the community, in a community center, or in the pool of patients already followed in our laboratory. SD patients were recruited from a larger project conducted in Quebec City (see Auclair-Ouellet et al, 2016). Participants in the HE group were recruited through public announcements and in two community centers in Quebec City.…”
Section: Methods Participantsmentioning
confidence: 99%